Diseño Lumínico para el Estadio de la Universidad Nacional de Loja - Carpio González, Byron Rafael (2019)
In the present titling work the light design is carried out for the stadium of the National University of Loja, in the project it is required to illuminate the area of the 6 400 m² soccer field, in addition to the hallways and bleachers, this design is carried out according to the recommendations and regulations of the International Federation of Associated Football (FIFA), and technical documentation concerning the lighting of sports venues to determine the levels of lighting, uniformity, mounting height, types of luminaires, tower positioning, etc. Three lighting design proposals are considered which are: with LED technology of 520 W of power per luminaire, with metal halide luminaires of 2 000 W of power per luminaire and with high pressure mercury luminaires of 2 123 W of power per luminary. For the selection of the lighting system, the economic technical analysis was carried out where the technical characteristics, number of luminaires, energy consumption and useful life of each type of luminaire were considered, obtaining a VAC of 327 493,88 USD in a period of 20 years for the proposal with metal halide luminaires, this being the one with the lowest expenses. The simulation of the lighting system for the soccer field with metal halides was obtained, obtaining a coefficient of uniformity 1 of 0,85, a coefficient of uniformity 2 of 0,92 and an average illuminance of 765 lux, determining that the system complies with FIFA regulations. Keywords: Light design, uniformity, economic technical analysis, social cost, DIALux evo ®.